Peningkatan Adopsi Teknologi: Branding dan Digitalisasi UMKM Cosmic Heaven - Pertiwi, Aprilla Putri; Muntaha, Ahmad (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
Cosmic Heaven, a Micro, Small, and Medium Enterprise (MSME), specializes in creating beaded accessories and merchandise. However, it faces constraints in digitalization and brand identity strengthening, making it difficult to reach a broader market. This Student Community Service (KKN) program was implemented to address these challenges through comprehensive brand strengthening, digital marketing optimization, and the provision of promotional media. The implementation methods included field observation, interviews, intensive mentoring, hands-on practice, and the production of marketing media. Activities ranged from problem identification and branding strategy design to creating a Shopee account, producing a Company Profile video, and developing physical banners for offline promotion. The results showed a significant improvement in the MSME's professional appearance, the establishment of a clearer visual identity, an increase in both digital and physical marketing materials, and enhanced understanding by the owner in managing content and utilizing digital platforms. Through this program, Cosmic Heaven gained a strong foundation to enhance its competitiveness, expand its marketing reach, and independently develop the business after the KKN program concludes.